Dynamics of circulating lipoproteins and lipids in Brown Skua (Stercorarius antarcticus lonnbergi) during the breeding cycle - Ibañez, Andres Esteban; Pasquevich, María Yanina; Fernandez Machulsky, Nahuel Hernan; Berg, Gabriela Alicia; Heras, Horacio; Montalti, Diego; Graña Grilli, Maricel (Polar Biology)
In central-place foragers the breeding cycle is often the period with the highest energy cost, where dietary and stored lipids play a key role. Lipids are mobilized through blood lipoproteins providing fuel to tissues. Thus, the use of food and endogenous resources with high-energy fats is important to sustain individuals’ nutritional demands. To evaluate the physiological components associated to energetic demands and their variation regarding life history processes, we analysed the plasma circulating lipoprotein levels, the lipid classes and fatty acid (FA) composition in Brown Skua (Stercorarius antarcticus lonnbergi) in breeding stages with different energy requirements: incubation (In), early rearing (Er) and late rearing (Lr). We expected to find differences according to the energy demands of each stage and the sex. The level of Very Low Density lipoproteins was affected by the sex and the breeding stage, whereas Low Density lipoproteins only by the stage. Total plasma lipid content and circulating lipid classes were invariant among the stages studied; however, differences in total plasma FA and monounsaturated FA (oleic and nervonic) abundances were observed among stages. Besides, a decrease in the n-3:n-6 ratio was observed towards the Lr stage. The differences found in lipoproteins may be linked to changes in the energy demands throughout the breeding period. Moreover, the variation observed in FA abundance and n-3:n-6 ratio may be related to a preferential mobilization of FA from stores as fuel or, possibly, to a differential use of the available food resources. Fil: Ibañez, Andres Esteban. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología de Vertebrados. Sección Ornitología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Pasquevich, María Yanina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Instituto de ...